Water-based low-temperature stoving varnish for heat dissipation module and preparation method thereof

By developing water-based low-temperature paint suitable for heat dissipation modules, and using fluorosilane to modify boron nitride/zinc oxide nanowire materials, the problems of poor adhesion and environmental hazards in traditional coating technology are solved, and excellent adhesion at high temperatures are achieved The combination with thermal conductivity reduces the cost of coating.

CN119242106APending Publication Date: 2025-01-03SUZHOU COLOR WAY ENTERPRISE DEV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411035327.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the existing heat dissipation module coating technology, oil-based paint causes solder to fall off and parts to fall apart during high-temperature baking, and poor adhesion. Traditional paintings have harmful effects to personal health and the environment, and it is difficult to meet the special basis of heat dissipation modules. Material attachment requirements.

Method used

Develop an aqueous low-temperature baking paint suitable for baking conditions of 90-110°C, using a combination of component A and component B, including deionized water, aqueous dispersants, carbon black powder, nanothermal conductive materials, defoaming agents, etc., and use Fluorosilane modified boron nitride/zinc oxide nanowire material provides excellent adhesion and thermal conductivity, and is suitable for surfaces such as copper, stainless steel, aluminum alloys, etc.

Benefits of technology

It achieves excellent adhesion on the surface of the heat dissipation module, reduces coating energy consumption, saves costs, avoids cracking in exposed areas of solder paste and rosin, enhances the thermal conductivity and stability of the coating, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a water-based low-temperature stoving varnish for a heat dissipation module and a preparation method thereof.The stoving varnish comprises a component A and a component B. The mass ratio of the component A to the component B is 100: (0.5-2.0), and the component A comprises, by mass, 10-20% of deionized water, 1-2% of a water-based dispersing agent, 2-5% of carbon black powder, 5-15% of filler, 5-8% of a nanometer heat conduction material, 0.1-0.5% of a defoaming agent and 0.5-1% of an anti-settling agent; the water-based paint is prepared from 40-60% of water-based hydroxy acrylic resin, 3-5% of an alcohol ether cosolvent, 1-5% of amino resin, 1-5% of water-based epoxy phosphate, 0.5-1% of matting powder, 0.2-0.5% of a wetting leveling agent, 0.5-2% of an anti-oil agent and 0.5-2% of a thickening agent. The nano heat conduction material is a fluorosilane modified boron nitride / zinc oxide nanowire material; and the component B comprises a water-based drying assistant. The baking varnish prepared by the invention is suitable for low-temperature baking, and has excellent adhesive force on various substrate surfaces and air outlets of the heat dissipation module. In addition, the water-based baking varnish disclosed by the invention has excellent wettability, and does not shrink or accumulate at greasy dirt on the surface of the heat dissipation module.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a water-based low-temperature baking varnish for a heat dissipation module and a preparation method thereof. Background Art

[0002] The heat dissipation module is a module unit used for heat dissipation of systems or devices. At present, it is used to refer specifically to the heat dissipation device of notebook computers. It is made of heat conduction plate, radiator, heat pipe and mounting frame bonded by solder paste and rosin. Applying a layer of anti-corrosion coating on the surface of the heat dissipation module can effectively increase its service life and service life. The surface coating of the heat dissipation module is usually done on an indoor assembly line. Traditional oil-based paint will produce a large amount of VOC during the coating and baking process, which will cause great harm to human health and the surrounding environment. The various components of the heat dissipation module are bonded by solder paste and rosin. High-temperature baking will cause problems such as solder shedding and parts falling apart. In addition, there is a certain amount of oil and solder residue on the surface of the bare parts of the heat dissipation module. If it is not cleaned up, it is easy to cause problems such as sagging, shrinkage, accumulation and poor adhesion. Because the heat dissipation module is assembled from a variety of special substrates such as copper, stainless steel, aluminum alloy and zinc alloy, it has high requirements for the adhesion of the coating paint. Therefore, it is necessary to develop a water-based low-temperature baking paint that can effectively solve the above technical problems while meeting the construction conditions. Summary of the invention

[0003] The technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a water-based low-temperature baking varnish for a heat dissipation module and a preparation method thereof are provided. The baking varnish prepared by the present invention is suitable for baking conditions of 90-110°C, reduces coating energy consumption, saves coating costs, and does not damage the substrate of the heat dissipation module. The water-based baking varnish provided by the present invention has excellent adhesion on the copper-based, stainless steel, aluminum alloy, zinc alloy surfaces and air outlets of the heat dissipation module, and does not slip or crack at the exposed areas of the solder paste and rosin of the heat dissipation module. In addition, the water-based baking varnish of the present invention has excellent wetting properties, and does not shrink or accumulate at the oily areas on the surface of the heat dissipation module.

[0004] In order to solve the above technical problems, the technical solution of the present invention is:

[0005] A water-based low-temperature baking varnish for a heat dissipation module comprises a component A and a component B, wherein the mass ratio of the component A to the component B is 100:(0.5-2.0), and the component A comprises the following components in terms of mass percentage:

[0006] 10-20% deionized water, 1-2% aqueous dispersant, 2-5% carbon black powder, 5-15% filler, 5-8% nano thermal conductive material, 0.1-0.5% defoamer, 0.5-1% anti-settling agent, 40-60% aqueous hydroxy acrylic resin, 3-5% alcohol ether cosolvent, 1-5% amino resin, 1-5% aqueous epoxy phosphate, 0.5-1% matting powder, 0.2-0.5% wetting and leveling agent, 0.5-2% anti-oil agent, 0.5-2% thickener; the nano thermal conductive material is fluorosilane modified boron nitride / zinc oxide nanowire material;

[0007] The component B comprises an aqueous drying aid.

[0008] Preferably, the aqueous dispersant is a nonionic dispersant; and / or the carbon black is one of medium-pigment carbon black and high-pigment carbon black, or a mixture of the two; and / or the filler is one of barium sulfate and talc; and / or the anti-settling agent is one of bentonite and fumed silica.

[0009] Preferably, the waterborne hydroxy acrylic resin has a solid content of 40-45%, and a hydroxyl content of 1-4% in the waterborne hydroxy acrylic resin solid. Further, the waterborne hydroxy acrylic resin is a mixture of one or more of a primary dispersion, a secondary dispersion, and an emulsion.

[0010] Preferably, the alcohol ether cosolvent is a mixture of one or more of ethanol, ethylene glycol butyl ether, diethylene glycol butyl ether, propylene glycol methyl ether, dipropylene glycol methyl ether and dipropylene glycol butyl ether.

[0011] Preferably, the amino resin is a methyl etherified amino resin, has a solid content of 70-80%, and a deblocking temperature of 80-90°C.

[0012] Preferably, the anti-oil agent is an isoparaffin rheological agent.

[0013] Preferably, the aqueous thickener is a mixture of one or more polyurethane low shear thickeners, polyurethane medium shear thickeners, and polyurethane high shear thickeners.

[0014] Preferably, the aqueous drying aid is one of aziridine, polycarbodiimide and an acid catalyst. Further, the acid catalyst is blocked p-toluenesulfonic acid, and its deblocking temperature is 80-90°C.

[0015] Preferably, the method for preparing the nano thermal conductive material comprises the following steps:

[0016] 1. calcining boron nitride powder in air atmosphere to obtain hydroxylated boron nitride;

[0017] 2. Mix the zinc acetate solution and the sodium hydroxide solution evenly under vigorous stirring, then add hydroxylated boron nitride, continue stirring, and finally filter, wash and dry the precipitate to obtain seed crystals;

[0018] 3. adding the seed crystals to a mixed solution of zinc nitrate hexahydrate, hexamethylenetetramine, polyethyleneimine and deionized water, heating the mixture to react, and after the reaction is completed, cooling the reaction solution to room temperature and filtering the mixture, washing the precipitate and drying the mixture to obtain a boron nitride / zinc oxide nanowire composite material;

[0019] Fourth, adding fluorosilane to an ethanol solution for hydrolysis treatment, then adding the above-mentioned boron nitride / zinc oxide nanowire composite material to react, filtering the reaction solution after the reaction is completed, washing the precipitate, and drying to obtain a nano thermal conductive material.

[0020] Preferably, in step 1, the calcination conditions include at least one of the following characteristics:

[0021] The calcination temperature is 800°C and the calcination time is 3-6h;

[0022] The heating rate during the calcination treatment is 5-10°C / min.

[0023] Preferably, in step 2, the zinc acetate solution is a zinc acetate ethanol solution with a concentration of 0.03 mol / L, the sodium hydroxide solution is a sodium hydroxide ethanol solution with a concentration of 0.04 mol / L, and the volume ratio of the zinc acetate solution to the sodium hydroxide solution is 1:1.

[0024] Preferably, in step 2, the temperature for uniform mixing is 60-70°C, and the time for uniform mixing is 30-40 min; the temperature for continued stirring is 60-70°C, and the time for continued stirring is 4-6 h; the stirring speed during uniform mixing and continued stirring is 2000-3000 r / min.

[0025] Preferably, in step 3, the mass ratio of seed crystal, zinc nitrate hexahydrate, hexamethylenetetramine and polyethyleneimine is 1:(3-4):(1-2):(0.5-1).

[0026] Preferably, in step three, the temperature of the temperature-raising reaction is 90-100° C., and the time of the temperature-raising reaction is 4-6 h.

[0027] Preferably, the concentration of the ethanol solution is 90-95wt%, the volume ratio of the fluorosilane and the ethanol solution is (0.5-1):100, the temperature of the hydrolysis treatment is 60°C, and the time of the hydrolysis treatment is 0.5-1h.

[0028] Preferably, in step 4, the usage ratio of the fluorosilane and boron nitride / zinc oxide nanowire composite material is (0.5-1) ml: (2-4) g, the reaction temperature is 80° C., and the reaction time is 1-2 h.

[0029] In order to better solve the above technical problems, the present invention also discloses the following technical solutions:

[0030] A method for preparing a water-based low-temperature baking varnish for a heat dissipation module comprises the following steps:

[0031] (1) Mixing deionized water, aqueous dispersant, carbon black powder, filler, nano thermal conductive material, defoamer, and anti-settling agent in percentage by mass, uniformly dispersing at high speed, and grinding with a sand mill to obtain a slurry;

[0032] (2) mixing the ground slurry with water-based hydroxy acrylic resin, alcohol ether cosolvent, amino resin, water-based epoxy phosphate, matting powder, wetting and leveling agent, anti-oil agent, and thickener, stirring and dispersing evenly to obtain a water-based low-temperature baking paint component A;

[0033] (3) A water-based drying aid is used as the B component of the water-based low-temperature baking varnish.

[0034] Preferably, in step (1), the fineness of the slurry is less than 20 μm.

[0035] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0036] The present invention provides a water-based low-temperature baking varnish for surface coating of a heat dissipation module. The water-based low-temperature baking varnish has excellent adhesion on copper-based, stainless steel, aluminum alloy, zinc alloy surfaces and air outlets, does not slip or crack at exposed areas of solder paste and rosin, does not shrink or accumulate at oily areas on the surface of the heat dissipation module, is suitable for baking conditions of 90-110°C, reduces coating energy consumption, and saves coating costs.

[0037] Under the premise of ensuring the excellent adhesion of water-based low-temperature baking varnish, in order to improve the thermal conductivity of baking varnish, the present invention also adds a certain amount of nano thermal conductive material to the baking varnish, and the nano thermal conductive material is a fluorosilane-modified boron nitride / zinc oxide nanowire material, which has a large specific surface area. After being uniformly dispersed in the coating matrix, it can provide more contact points and cross-linking sites, thereby enhancing the adhesion of the coating. Moreover, the boron nitride and zinc oxide nanowire materials themselves have excellent thermal conductivity. When added to the coating matrix, the thermal conductivity of the coating can be significantly improved. When added to the coating matrix, it can effectively promote the conduction and dispersion of heat, thereby reducing the temperature gradient on the coating surface, reducing the stress and deformation caused by temperature changes, and improving the stability and durability of the coating. Moreover, the boron nitride and zinc oxide nanowire materials can form a uniform and dense protective layer, effectively preventing the erosion of moisture, oxygen and chemical substances, thereby extending the service life of the coating and improving the effect of protecting the surface. DETAILED DESCRIPTION

[0038] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0040] In the following examples, the performance parameters of each raw material are as follows, and other raw materials are commercially available unless otherwise specified.

[0041] Boron nitride powder: hexagonal boron nitride, average particle size 3-5μm;

[0042] Polyethyleneimine: weight average molecular weight is 600;

[0043] Aqueous dispersant: non-ionic aqueous dispersant ECO-2800, purchased from Dongguan Wanying New Materials Co., Ltd.; defoamer: HT-50 durable defoamer for water-based coatings, purchased from Nantong Hantai Chemical Co., Ltd.; water-based hydroxyl acrylic resin: PA-4000, hydroxyl content 1.0%, solid content 45%, purchased from Guangzhou Guanzhi New Materials Technology Co., Ltd.; amino resin: BR892 methyl etherified amino resin, solid content 70-80%, unblocking temperature 80-90°C, purchased from Changchun Chemical (Jiangsu) Co., Ltd.; water-based epoxy phosphate: epoxy phosphate RKZ3008, purchased from Tianjin Ruike Chemical Trading Co., Ltd.; matting powder: Tosoh matting powder E-1011, Shanghai Kaiyin Chemical Co., Ltd.; wetting and leveling agent: Digo TEGO Glide410 leveling agent, Shanghai Kaiyin Chemical Co., Ltd.; isoparaffin rheological agent: NP-40, purchased from Guangzhou Guanzhi New Materials Technology Co., Ltd.

[0044] Example 1

[0045] A method for preparing a water-based low-temperature baking varnish for a heat dissipation module comprises the following steps:

[0046] S1: Preparation of nano thermal conductive materials:

[0047] The boron nitride powder is placed in a muffle furnace, heated to 800°C at a heating rate of 10°C / min in an air atmosphere, and calcined for 5 hours to obtain hydroxylated boron nitride;

[0048] 50 ml of 0.03 mol / L zinc acetate ethanol solution and 50 ml of 0.04 mol / L sodium hydroxide ethanol solution were mixed at 65°C and 2000 r / min for 30 min, then 1.25 g of hydroxylated boron nitride was added, and the mixture was stirred at 65°C and 2000 r / min for 5 h, and finally filtered, the precipitate was washed and dried to obtain seed crystals;

[0049] 1 g of seed crystals was added to a mixed solution consisting of 3.7 g of zinc nitrate hexahydrate, 1.8 g of hexamethylenetetramine, 0.5 g of polyethyleneimine, and 100 ml of deionized water, and the temperature was raised to 95° C. for reaction for 5 h. After the reaction was completed, the reaction solution was cooled to room temperature and filtered, and the precipitate was washed and dried to obtain a boron nitride / zinc oxide nanowire composite material;

[0050] 0.5 ml of fluorosilane was added to 100 ml of 95 wt% ethanol solution, and the solution was hydrolyzed at 60° C. for 1 h. Then 3 g of the boron nitride / zinc oxide nanowire composite material was added and reacted at 80° C. for 2 h. After the reaction, the reaction solution was filtered, and the precipitate was washed and dried to obtain a nano thermal conductive material.

[0051] S2: Preparation of water-based resin-free slurry:

[0052] While stirring at high speed, add the following raw materials in sequence: 200 g of deionized water, 20 g of aqueous dispersant, 20 g of high-pigment carbon black powder, 50 g of talcum powder, 50 g of nano-thermal conductive material, 1 g of defoamer, and 10 g of fumed silica, disperse until uniform, and grind to a fineness of less than 20 μm to obtain a water-based resin-free slurry;

[0053] S3: Preparation of water-based low-temperature baking varnish:

[0054] While stirring, 520g of water-based hydroxy acrylic resin, 25g of ethylene glycol butyl ether, 25g of diethylene glycol butyl ether, 20g of amino resin, 20g of water-based epoxy phosphate, 5g of matting powder, 4g of wetting and leveling agent, 20g of isoparaffin rheological agent, and 10g of water-based polyurethane low-shear thickener were added to the water-based resin-free slurry in sequence to prepare water-based low-temperature baking paint component A; 10g of aziridine was weighed as water-based low-temperature baking paint component B.

[0055] Example 2

[0056] A method for preparing a water-based low-temperature baking varnish for a heat dissipation module comprises the following steps:

[0057] S1: Preparation of nano thermal conductive materials:

[0058] Same as Example 1

[0059] S2: Preparation of water-based resin-free slurry:

[0060] Same as Example 1

[0061] S3: Preparation of water-based low-temperature baking varnish:

[0062] The preparation process of component A is the same as that of Example 1, and component B is 10 g of polycarbodiimide.

[0063] Example 3

[0064] A method for preparing a water-based low-temperature baking varnish for a heat dissipation module comprises the following steps:

[0065] S1: Preparation of nano thermal conductive materials:

[0066] Same as Example 1;

[0067] S2: Preparation of water-based resin-free slurry:

[0068] While stirring at high speed, add the following raw materials in sequence: 200g deionized water, 20g aqueous dispersant, 20g high-pigment carbon black powder, 50g talcum powder, 50g nano-thermal conductive material, 1g defoamer, and 10g fumed silica, disperse until uniform, and grind to a fineness of less than 20 microns to obtain a water-based resin-free slurry.

[0069] S3: Preparation of water-based low-temperature baking varnish:

[0070] While stirring, 500g of water-based hydroxy acrylic resin, 25g of ethylene glycol butyl ether, 25g of diethylene glycol butyl ether, 40g of amino resin, 20g of water-based epoxy phosphate, 10g of matting powder, 4g of wetting and leveling agent, 20g of isoparaffin rheological agent, and 5g of water-based polyurethane thickener were added to the water-based resin-free slurry in sequence to prepare water-based low-temperature baking paint component A; 5g of blocked p-toluenesulfonic acid was weighed as water-based low-temperature baking paint component B.

[0071] In order to better verify that the water-based low-temperature baking varnish provided by the present invention has better performance, a plurality of comparative examples are given below for detailed comparative description.

[0072] Comparative Example 1

[0073] Compared with Example 1, in step S3, no water-based epoxy phosphate is added, and the other steps are the same as those in Example 1.

[0074] From the test results in Table 1, it can be seen that the prepared paint film has excellent adhesion on the copper substrate, but poor adhesion on the surfaces of stainless steel, aluminum alloy and zinc alloy substrates, and the cross-hatch test results are ≥ level 2.

[0075] Comparative Example 2

[0076] Compared with Example 1, in step S3, no anti-oil agent is added, and the other steps are the same as Example 1. Shrinkage holes occasionally appear on the surface of the paint film.

[0077] Comparative Example 3

[0078] Compared with Example 1, in step S3, the waterborne polyurethane low shear thickener is replaced with an alkali swelling thickener, the model of which is BASF AS1130, and the solid content is 30%.

[0079] Comparative Example 4

[0080] Compared with Example 1, in step S1, fluorosilane is not used for modification, and other conditions are the same as those in Example 1.

[0081] Comparative Example 5

[0082] Compared with Example 1, in step S1, fluorosilane is used to directly modify hydroxylated boron nitride, zinc oxide nanowires are not included, and other conditions are the same as in Example 1.

[0083] Comparative Example 6

[0084] Compared with Example 1, in step S1, fluorosilane is used to modify the zinc oxide nanowires, and hydroxylated boron nitride is not added. Other conditions are the same as in Example 1.

[0085] The water-based low-temperature baking varnish prepared in the above embodiment and comparative example was applied to the surface of the heat dissipation module, and the specific construction parameters were as follows: coating method: compressed air spraying, spraying film thickness was 30-40 μm; construction viscosity: coating four cups for 60-90 seconds; baking conditions: baking at 105°C for 15 minutes. The performance of the above coating was tested, and the test method and test results are as follows:

[0086] The dried paint film was tested, and the test results are shown in Table 1.

[0087] Table 1

[0088]

[0089]

[0090]

[0091] It can be seen from the above test results that compared with the comparative example, the paint films prepared in Examples 1-3 have a smooth appearance, no orange peel, no shrinkage cavities, no slipping paint at the rosin and solder paste, and no cracking. In Comparative Example 1, no water-based epoxy phosphate is added, and the adhesion of the paint film is also reduced. This is mainly because the water-based epoxy phosphate has an epoxy group, which can undergo a cross-linking reaction with groups such as hydroxyl or amino groups during the coating curing process. This cross-linking reaction can form a three-dimensional network structure, thereby improving the strength and toughness of the coating and improving the adhesion. In Comparative Example 2, no anti-oil stain agent is added, the wetting and leveling properties of the paint film deteriorate, and shrinkage cavities appear on the surface. In Comparative Example 3, an alkali swelling thickener is used, and the surface of the prepared paint film is uneven, the orange peel degree is high, and the appearance effect is not good. It can be seen from Comparative Examples 4-6 that the addition of nano-thermal conductive materials has no effect on the appearance, adhesion, weather resistance, etc. of the paint film, and will improve the thermal conductivity of the paint film to a certain extent. The improvement of thermal conductivity mainly depends on the compatibility of nano-thermal conductive materials and the coating matrix. In comparative example 4, no fluorosilane was added for modification, and the thermal conductivity of the paint film was slightly reduced, mainly because the grafting of fluorosilane can effectively reduce the surface energy of the material, thereby changing the material from hydrophilic to hydrophobic, thereby improving the compatibility of the material with the coating matrix. In comparative example 5, no zinc oxide nanowires were added, and no hydroxylated boron nitride was added in the comparative example, and the thermal conductivity of the paint film was significantly reduced, which shows that the addition of zinc oxide nanowires and hydroxylated boron nitride as thermal conductive fillers in the present invention has a certain synergistic effect, mainly because when the two-dimensional material hydroxylated boron nitride is compounded with the one-dimensional material zinc oxide nanowire, the zinc oxide nanowire will enter the interlayer of the hydroxylated boron nitride, increase the interlayer spacing of the hydroxylated boron nitride, and then improve the dispersibility of the material, thereby forming a more stable thermal conductive network and improving the thermal conductivity of the paint film.

[0092] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A water-based low-temperature paint for a heat dissipation module, characterized in that: The invention comprises component A and component B, wherein the mass ratio of component A to component B is 100:(0.5-2.0), and component A comprises the following components in terms of mass percentage: 10-20% deionized water, 1-2% aqueous dispersant, 2-5% carbon black powder, 5-15% filler, 5-8% nano thermal conductive material, 0.1-0.5% defoamer, 0.5-1% anti-settling agent, 40-60% aqueous hydroxy acrylic resin, 3-5% alcohol ether cosolvent, 1-5% amino resin, 1-5% aqueous epoxy phosphate, 0.5-1% matting powder, 0.2-0.5% wetting and leveling agent, 0.5-2% anti-oil agent, 0.5-2% thickener; the nano thermal conductive material is fluorosilane modified boron nitride / zinc oxide nanowire material; The component B comprises an aqueous drying aid.

2. The water-based low-temperature baking varnish for heat dissipation module according to claim 1, characterized in that: The aqueous dispersant is a nonionic dispersant; and / or the carbon black is one of medium-pigment carbon black and high-pigment carbon black, or a mixture of the two; and / or the filler is one of barium sulfate and talcum powder; and / or the anti-settling agent is one of bentonite and fumed silica.

3. The water-based low-temperature baking varnish for heat dissipation module according to claim 1, characterized in that: The solid content of the water-based hydroxylated acrylic resin is 40-45%, and the hydroxyl content in the water-based hydroxylated acrylic resin solid is 1-4%; and / or the alcohol ether cosolvent is a mixture of one or more of ethanol, ethylene glycol butyl ether, diethylene glycol butyl ether, propylene glycol methyl ether, dipropylene glycol methyl ether, and dipropylene glycol butyl ether.

4. The water-based low-temperature baking varnish for heat dissipation module according to claim 1, characterized in that: The amino resin is a methyl etherified amino resin with a solid content of 70-80% and a deblocking temperature of 80-90°C; and / or the anti-oil agent is an isoparaffin rheological agent; and / or the water-based thickener is a mixture of one or more polyurethane low-shear thickeners, polyurethane medium-shear thickeners, and polyurethane high-shear thickeners; and / or the water-based drying aid is one of aziridine, polycarbodiimide, and an acid catalyst.

5. The water-based low-temperature baking varnish for heat dissipation module according to claim 1, characterized in that: The preparation method of the nano thermal conductive material comprises the following steps:

1. calcining boron nitride powder in air atmosphere to obtain hydroxylated boron nitride; 2. Mix the zinc acetate solution and the sodium hydroxide solution evenly under vigorous stirring, then add hydroxylated boron nitride, continue stirring, and finally filter, wash and dry the precipitate to obtain seed crystals; 3. adding the seed crystals to a mixed solution of zinc nitrate hexahydrate, hexamethylenetetramine, polyethyleneimine and deionized water, heating the mixture to react, and after the reaction is completed, cooling the reaction solution to room temperature and filtering the mixture, washing the precipitate and drying the mixture to obtain a boron nitride / zinc oxide nanowire composite material; Fourth, adding fluorosilane to an ethanol solution for hydrolysis treatment, then adding the above-mentioned boron nitride / zinc oxide nanowire composite material to react, filtering the reaction solution after the reaction is completed, washing the precipitate, and drying to obtain a nano thermal conductive material.

6. The water-based low-temperature baking varnish for heat dissipation module according to claim 5, characterized in that: In step 1, the calcination conditions include at least one of the following characteristics: The calcination temperature is 800°C and the calcination time is 3-6h; The heating rate during the calcination treatment is 5-10°C / min.

7. The water-based low-temperature baking varnish for heat dissipation module according to claim 5, characterized in that: In step 2, the zinc acetate solution is a zinc acetate ethanol solution with a concentration of 0.03 mol / L, the sodium hydroxide solution is a sodium hydroxide ethanol solution with a concentration of 0.04 mol / L, and the volume ratio of the zinc acetate solution to the sodium hydroxide solution is 1:1; and / or the temperature for uniform mixing is 60-70°C, and the time for uniform mixing is 30-40 min; and / or the temperature for continued stirring is 60-70°C, and the time for continued stirring is 4-6 h; and / or the stirring speed during uniform mixing and continued stirring is 2000-3000 r / min.

8. The water-based low-temperature baking varnish for heat dissipation module according to claim 5, characterized in that: In step 3, the mass ratio of seed crystal, zinc nitrate hexahydrate, hexamethylenetetramine and polyethyleneimine is 1:(3-4):(1-2):(0.5-1); and / or the temperature of the temperature heating reaction is 90-100° C., and the time of the temperature heating reaction is 4-6 hours.

9. The water-based low-temperature baking varnish for heat dissipation module according to claim 5, characterized in that: In step 4, the concentration of the ethanol solution is 90-95wt%, the volume ratio of the fluorosilane and the ethanol solution is (0.5-1):100; and / or the temperature of the hydrolysis treatment is 60°C, and the time of the hydrolysis treatment is 0.5-1h; and / or the amount ratio of the fluorosilane and the boron nitride / zinc oxide nanowire composite material is (0.5-1)ml:(2-4)g, and / or the reaction temperature is 80°C, and the reaction time is 1-2h.

10. A method for preparing a water-based low-temperature baking varnish for a heat dissipation module according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Mixing deionized water, aqueous dispersant, carbon black powder, filler, nano thermal conductive material, defoamer, and anti-settling agent in percentage by mass, uniformly dispersing at high speed, and grinding with a sand mill to obtain a slurry; (2) mixing the ground slurry with water-based hydroxy acrylic resin, alcohol ether cosolvent, amino resin, water-based epoxy phosphate, matting powder, wetting and leveling agent, anti-oil agent, and thickener, stirring and dispersing evenly to obtain a water-based low-temperature baking paint component A; (3) A water-based drying aid is used as the B component of the water-based low-temperature baking varnish.

Citation Information

Patent Citations

  • Feasible-thickness waterborne amino baking paint as well as preparation method and application thereof

    CN108707380A

  • Waterborne amino paint and preparation method thereof

    CN109897487A

  • Anticorrosive waterborne heat dissipation coating and preparation method thereof

    CN110066563A

  • Boron nitride nanotube loaded nano zinc oxide material and preparation method thereof

    CN115363047A

  • Water-based heat-conducting coating

    CN117625015A